2009
DOI: 10.2174/138161209787315738
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Lowering Drugs Acting at the Level of the Gastrointestinal Tract

Abstract: This review considers the hypolipidaemic drugs that act on the gastrointestinal (GI) tract. We searched PubMed up to April 2008 and included randomized controlled trials, original papers, review articles and case reports. Bile acid sequestrants (BAS) have a well-established low density lipoprotein cholesterol (LDL-C) lowering effect, but may increase triglyceride (TG) levels. BAS have no systematic adverse effects, but are associated with increased GI adverse effects and interactions with the absorption of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 337 publications
(542 reference statements)
0
23
0
3
Order By: Relevance
“…Ezetimibe, a specific inhibitor of cholesterol absorption, is widely used for the treatment of dyslipidemia as monotherapy or given with a statin (12 …”
Section: Statins 3-hydroxy-3-methylglutaryl Coenzyme a (Hmgcoa) Redumentioning
confidence: 99%
“…Ezetimibe, a specific inhibitor of cholesterol absorption, is widely used for the treatment of dyslipidemia as monotherapy or given with a statin (12 …”
Section: Statins 3-hydroxy-3-methylglutaryl Coenzyme a (Hmgcoa) Redumentioning
confidence: 99%
“…After 4.9 years (median) the simvastatin and ezetimibe combination significantly reduced major atherosclerotic vascular events by 17% (p ¼ 0.0021) compared with placebo 37 . Combining lipid-lowering drugs acting at the level of the gastrointestinal tract could help statin-intolerant patients 38 . A retrospective study showed that the combination of colesevelam (1.875 g twice daily) with ezetimibe significantly reduced LDL-C levels by 42% in 16 patients with diabetes or metabolic syndrome and a history of statin intolerance, after 3 months of treatment 39 .…”
Section: Efficacymentioning
confidence: 99%
“…Ezetimibe belongs to a class of hypolipidemic agents, the cholesterol absorption inhibitors, which inhibit cholesterol absorption from the intestinal lumen into enterocytes [6] . The molecular target of ezetimibe is the sterol transporter Niemann-Pick C1-like 1 protein (NPC1L1) [7,8] .…”
Section: Role Of Ezetimibe In Nafldmentioning
confidence: 99%
“…Ezetimibe in the setting of hyperlipidemia is usually given combined with other hypolipidemic drugs [6] , which leads to complementary results in terms of cardiovascular disease risk factors due to the different mechanisms of action. The combination of ezetimibe with other interventions seems to be beneficial in NAFLD patients.…”
Section: Role Of Drug Combinations Including Ezetimibe In Nafldmentioning
confidence: 99%